2019
DOI: 10.1038/s41598-019-48390-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Scandium Phosphate after Peroxide Assisted Leaching of Iron Depleted Bauxite Residue (Red Mud) Slags

Abstract: Anticipated future demand and limited primary sources of Sc highlight the importance of secondary Sc resources such as bauxite residue (red mud). In this study, a process route starting from red mud aiming to recover Sc as a concentrate by a combination of pyrometallurgical and hydrometallurgical processes was developed. Bauxite residue was treated in an electric arc furnace (EAF) for Fe removal as well as slag conditioning with varying flux additions and various cooling conditions. 95% of iron recovery to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The leaching by the mixture of 2.5 M H 2 O 2 and 2.5 M H 2 SO 4 at 90 • C and an S/L ratio of 1/10 for 30 min resulted in the recovery of 68% Sc and 91% Ti; the yield of Fe and Al in the sulfuric acid solution was 23% and 43%, respectively. Some authors [59,60] have attempted to combine pyro-and hydrometallurgical methods aimed to reduce and remove iron in metallic form from the process, because, due to significant iron content compared to REEs both in red mud and in leached solutions, it is the main hindering factor for the separation and subsequent processing of the solutions. However, leaching of the slags from reduction smelting, which can be essentially considered REE preconcentrates, is complicated.…”
Section: Direct Acid Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaching by the mixture of 2.5 M H 2 O 2 and 2.5 M H 2 SO 4 at 90 • C and an S/L ratio of 1/10 for 30 min resulted in the recovery of 68% Sc and 91% Ti; the yield of Fe and Al in the sulfuric acid solution was 23% and 43%, respectively. Some authors [59,60] have attempted to combine pyro-and hydrometallurgical methods aimed to reduce and remove iron in metallic form from the process, because, due to significant iron content compared to REEs both in red mud and in leached solutions, it is the main hindering factor for the separation and subsequent processing of the solutions. However, leaching of the slags from reduction smelting, which can be essentially considered REE preconcentrates, is complicated.…”
Section: Direct Acid Digestionmentioning
confidence: 99%
“…Yagmurlu et al [59] tested six slag samples for selective recovery of REEs that were obtained by reduction smelting of red mud with fluxes, lime, or silica, at different rates of cooling rates, water quenching, or slow cooling. Table 2 demonstrates the chemical composition of red mud and the slags.…”
Section: Direct Acid Digestionmentioning
confidence: 99%
“…Elements such as Ce and Y present in AMD precipitates under the effect of RM enriching the mineral phase. Several authors had explored a pyrometallurgical treatment of BR to recover pig iron and enhance the content of critical raw material (CRM) in the final slag [100][101][102]. This approach can be beneficial to increase both pig iron and CRM from the filter cakes produce after coagulating AMD ions into an BR matrix.…”
Section: Recovery Of Yttrium Oxide From Waste Materialsmentioning
confidence: 99%
“…For chemical leaching, it has already been shown that the most potent leaching agent is peroxosulfuric / persulfuric acid, which can be formed by mixing sulfuric acid and hydrogen peroxide [9][10][11]. A logical continuation of this approach was the metal leaching with mixture of sulfuric acid, hydrogen peroxide, and organic acids [12]. This attempt simultaneously maintained a high acidity of the environment and simplified disposal of the wastes.…”
Section: Introductionmentioning
confidence: 99%